Investigation on prestressed concrete sleeper (PCS) subjected to dynamic loading on site and experimental works - Mohd Ikmal Fazlan Rozli; Che Mohd Hilmi Safiuddin Che Mohd Jamaludin; Juhaizad Ahmad; Abdul Samad Abdul Rahman; Kay Dora Abd. Ghani (Penerbit Universiti Kebangsaan Malaysia, 2022)
The purpose of the research was to study the condition of prestressed monoblock concrete sleeper (PMCS) under dynamic loading experimentally and through site investigation. From this research, the value of deflection base on acceleration of concrete sleepers have been obtained. This study showed the possible correlation and relation of the PCS deflection located under a railway track. This research includes experimentation process which includes experimental investigations for dynamic loading of prestressed concrete sleepers (PCS) were examined in terms of its capability to accommodate their own design capacity and the relationships between load and displacement happened within the concrete sleeper. This study will help the railway authorities to understand and take any maintenance action to their rail infrastructure. From experimental test, the highest deflection on KTMB and EPMI rail seat section is 1.35 mm and 1.04 mm respectively. From site investigation at KM20.75, the highest deflection occured is 5.993 mm which is lower compared to the highest deflection at KM26.25 with the value of 7.06 mm.